STEM-19. LIVE DETECTION OF NEURAL STEM AND GLIOBLASTOMA CELLS BY A LUMINESCENT CONJUGATED OLIGOTHIOPHENE DERIVATIVE. (14th November 2022) - Ilkhanizadeh, Shirin; Gracias, Aileen; Åslund, Andreas K O; Bäck, Marcus; Simon, Rozalyn; Neofytou, Christina; Rraklli, Vilma; Migliori, Bianca; Kavanagh, Edel; Nelander, Sven; Westermark, Bengt; Uhrbom, Lene; et al.
Abstract: Glioblastoma (GBM) is an aggressive nervous system tumor with a mean survival time of 12-14 months. Cells with neural stem cell-like properties can be derived from GBM tumors. These cells seem to escape conventional irradiation treatment, chemotherapy, and surgery, and may play a crucial role for relapse. It is therefore urgent to develop novel approaches for reliable detection of neural stem cell-like cells in GBM. Here we report a luminescent conjugated oligothiophene (LCO), named GlioStem (p-HTMI), for non-invasive and non-amplified real-time detection of live human patient-derived GBM cells and embryonic neural stem/progenitor cells (NSPCs). Within a maximum of 10 minutes after administration of the molecule in vitro, in the existing media, fluorescence emission was observed without any modulation of the cells or additional vehicle, resulting in efficient detection of cytoplasmic luminescent signal in NSPCs or GBM cells from rodents and humans, detectable at Alexa488/GFP wavelength. GlioStem is functionalized with a methylated imidazole moiety resembling the side chain of histidine/histamine, and non-methylated analogues were not functional. In vitro, GlioStem was shown to identify fetal cortical NSPCs from rat (FGF2-expanded), embryonic stem cell-derived NSPCs from mouse (FGF2/EGF-expanded), and FGF2-exposed C6 glioma cell cultures from rat, but not any other cell types investigated. Cell sorting experiments of patient-derived, FGF2/EGF-expanded GBM cells demonstrated that GlioStem in addition to NSPC-markers like Nestin and Sox2 labeled the same population (overlap > 90%) of cells as CD271, a proposed marker for stem cell-like cells and rapidly migrating cells in glioblastoma. Our results suggest that the LCO GlioStem is a versatile tool for immediate and selective detection of subpopulations of neural stem and glioma cells.